Sharing Magic Tricks among Librarians as a Process of Knowledge Preservation in Children Library services, Perpustakaan Nasional RI - Sutrilastio,; Salim, Tamara Adriani Susetyo (Journal of Strategic and Global Studies, 2018)
Magic show is performed to support Library Services in Perpustakaan Nasional RI. By using magic tricks combined with love reading values, children are invited and motivated to know the benefit of reading while encouraging to love reading. Unfortunately, magic tricks skill only be owned by one person. This condition make the services in library depend on one person. Realizing that conditions, the librarian named Abdul Rahim do something in order to make his magic tricks skill can be mastered by the other librarian namely being assistant, giving long and short mentoring, making video, writing article, and giving magic tools. This research uses qualitative method and literature study. It is committed to know how magic tricks skill are transmitted and taught to the other librarian by using SECI Model point of view namely Socialization, Internalization, Externalization and Combination. Based on the research the process which is conducted by Mr. Abdul Rahim in sharing the magic tricks can be categorized into SECI Model. This research as an encouragement to Perpustakaan Nasional to indicate, facilitate, respect and appreciate each tacit knowledge which is owned by librarian so that it can give benefit to the institution.